Взаємодія бурильної колони зі стінками свердловини в місцях утворення жолобів та каверн - Рачкевич, Р.В.; Козлов, А.А.; Сенчішак, В.М.; Тутко, Т.Ф.; Гриців, В.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
We consider stress-deformed state borehole of well on the walls wich is a gutter or cavity. Used model sufficient beams on the four pillars wich loaded both radial and axial efforts. The conclusions about the need this calculation in practice.